Characterizing defeat in observation-based defeasible logic programming - Capobianco, Marcela (2004)
In this work we analyze the problem of incorporating specificity to characterize defeat in a particular argumentative framework, called observation based defeasible logic programming (ODeLP) [1]. Eficiency is an important issues in ODeLP, since this framework has been de ned for representing the knowledge of intelligent agents in real world applications. Computing specificity using domain knowledge is a demanding operation. Thus, have devised a new version of this criterion, that optimizes the computation of the defeat relation.